2021
DOI: 10.1002/app.51908
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of triethyl citrate plasticized chitosan‐based membranes for efficient release of curcumin

Abstract: In order to improve the release efficiency and physical properties of single polysaccharide membranes, two types of curcumin (Cur)‐loaded composite membranes have been successfully prepared through chitosan (CS)/carboxymethyl cellulose (CMC), CS/soluble starch (SS) with triethyl citrate (TEC) as a plasticizer. The structure and properties of the membranes were characterized by infrared spectroscopy, scanning electron microscopy, X‐ray diffraction, and thermogravimetry. The results of mechanical tests and drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Although no definitive evidence of health risks associated with DBDA and BehD exists, this study revealed the extensive presence of these plasticizers in plastic-bottle-packaged PCPs, which could raise attention on potential human exposure through consumption. TEC is used as a plasticizer in the formation of membranes . It is also a food additive used to stabilize foams, especially to improve the whipping properties of egg whites .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no definitive evidence of health risks associated with DBDA and BehD exists, this study revealed the extensive presence of these plasticizers in plastic-bottle-packaged PCPs, which could raise attention on potential human exposure through consumption. TEC is used as a plasticizer in the formation of membranes . It is also a food additive used to stabilize foams, especially to improve the whipping properties of egg whites .…”
Section: Resultsmentioning
confidence: 99%
“…TEC is used as a plasticizer in the formation of membranes. 51 It is also a food additive used to stabilize foams, especially to improve the whipping properties of egg whites. 52 In this study, TEC was detected in 90% of the SH samples and 100% of the HC samples, contributing to the highest mean peak areas of 1.24 × 10 08 and 3.00 × 10 08 among all classifications, respectively.…”
Section: Journal Of Thementioning
confidence: 99%
“…When the amount of EC and TEC increased, folding endurance that was positively correlated increased. Because of the high polymer matrix and plasticizer, EC and TEC might also make the film more flexible [23]. According to another report, adding more plasticizers to a plasticized polymer system decreased the force needed to break the films and the resistance to deformation because the presence of plasticizers reduced the interaction between polymer chains [24].…”
Section: Resultsmentioning
confidence: 99%